Pemikiran Hanslick tentang Estetika dan Kritik Musik - Sunarto Sunarto (PROMUSIKA, 2015)
Approaching the mid‐19th century began the aesthetics of music, especially Western music aesthetics as an independent science apart from philosophy. In the development of musical aesthetics are always closely related between philosophy and the philosopher. Discussion on the aesthetics of music can not be separated from some of the theories that have been developed by philosophers. Eduard Hanslick is a figure in the history of musical aesthetics of music included in ʺGroup Autonomisʺ. This group believes that music is a world of sounds organized and stand alone without any. For him and the group, the music is not the language of emotions or feelings. He then gave a sharp criticism against some composers include Richard Wagner and Anton Bruckner as a representative ʺGroup Heteronomisʺ who argue that music can be a means of expressing feelings, expressing ideas, or a certain atmosphere. According to the aesthetics of music is ʺabsoluteʺ (to the music itself). With absolutismenya, Hanslick criticized mercilessly composers heteronomis deems to have abused the music to be ʺprogramaʺ (music for something) ‐which he regarded as ʹcheap musicʹ. The rivalry between the two camps stream music aesthetics was known as The Great Debate.